Integration Of Moral Curriculum With Arabic Literature Stories And Parables Of The Qur'an QSP - Abdul Hamed, Kirembwe Rashid; Che Noh, Mohd Aderi bin; Ramlan, Siti Rosilawati binti; Ahmad, Sakinah Binti; Ismail, Hayati Binti; Ishak, Maziahtusima Binti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research investigated the morality restoration MR phenomenon for Muslim university students MUS using Qur’anic stories and parables QSP, divine textual analysis DTA, and (Al-Furqan). It is the phase (One) of ADDIE’s five-phase design. This phase (One) was adopted in this research to investigate MUS morality needs. It was integral to a significant research project to develop the morality restoration module MRM for MUS. This research was meant to identify the critical aspects of the proposed MRM for MUS. The study used descriptive methods and a stratified random MUS sample size (n=122) selected from Malaysia and Uganda. The 5-scaled Likert questionnaire was also used to collect the data. An overall Cronbach's alpha report for “MR Need Analysis Scales” MRNAS yielded the reliability coefficients for the two MUS samples’ statistics ranging from (r)=.971 to (r)=.655. The literature review asserted that applying QSP’s DTA enables humanity to extract the valid divine message from QSP and unveil the concealed divine insights from QSP. The literature discussion further asserted that QSP’s DTA should encompass Quranic terminologies, elements of QSP texts, contexts, geographical locations, and QSP text and time. The results showed a need to use QSP’s DTA and (Al-Fur’qan) for MRM developments. The discussions stressed the role of (Al-Fur’qan) in MRM developments as a yardstick for all moral factors influencing MRM content developments and instructional designs. The results also showed that MUS needs restoration of morality for nine basic purposes: religious, social, communication, education, business, self-satisfaction, diplomatic, security, and legal. The researchers recommended the development of MRM for MUS using QSP’s DTA as an MRM instructional drive for MUS. They specifically recommended (Al-Fur’qan) verses as yardsticks for moral factors influencing MRM content developments and applications.